2011
DOI: 10.1007/s00253-011-3347-7
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and biochemical characterization of DagA from Streptomyces coelicolor A3(2): an endo-type β-agarase producing neoagarotetraose and neoagarohexaose

Abstract: The DagA product of Streptomyces coelicolor is an agarase with a primary translation product (35 kDa) of 309 amino acids, including a 30-amino acid signal peptide. Although dagA expression in Streptomyces lividans under the control of its own set of promoters was previously reported, its enzymatic properties have never been elucidated. To develop an improved expression system for dagA, three types of strong promoters for the Streptomyces host were linked to dagA, and their efficiencies in DagA production were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 31 publications
2
45
0
Order By: Relevance
“…Among these hydrolytic enzymes, the GH16 family agarase (DagA) was identified in S. coelicolor A3(2) as a ␤-agarase that can hydrolyze agar into neoagarotetraose or neoagarohexaose as the final product (31). From genomic sequencing data for S. coelicolor A3(2), we found that Sco3487, annotated as a putative hydrolase, was a good agarase candidate belonging to the GH50 family.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among these hydrolytic enzymes, the GH16 family agarase (DagA) was identified in S. coelicolor A3(2) as a ␤-agarase that can hydrolyze agar into neoagarotetraose or neoagarohexaose as the final product (31). From genomic sequencing data for S. coelicolor A3(2), we found that Sco3487, annotated as a putative hydrolase, was a good agarase candidate belonging to the GH50 family.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction was stopped by cooling the test tube in an ice-cold water bath, and the absorbance at 540 nm was recorded. One unit of enzyme activity was defined as the amount of activity producing an A 540 of 0.001 after a 15-min incubation (31).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The agarolytic activity was measured by the 3,5-dinitrosalicylic acid (DNS) method as previously reported (Chi et al 2014;Temuujin et al 2011), with slight modification. Briefly, 10 μl of the enzyme solution was mixed with 390 μl of 10 mM potassium phosphate buffer (pH 7.0) plus 0.5 % agarose and incubated at 50°C for 10 min.…”
Section: Determination Of the Agarolytic Activity Of The Recombinant mentioning
confidence: 99%